A system of real-time neural recording and stimulation and its potential application in blood pressure modulation - Shen, Anruo; Li, Runhuan; Li, Yiran; Guo, Jinyao; Wang, Jiguang; Sui, Xiaohong (Frontiers in Medical Technology, 2022)
Hypertension is one of the most prevalent chronic diseases that affects more than 20% of the adult population worldwide, but fortunately, most of their blood pressure can be effectively controlled via drug treatment. However, there still remains 5 30% of patients clinically who do not respond well to conventional medication while the non-drug treatments currently existing are struggling with major drawbacks like irreversible nerve damage, huge side effects and even non-effectiveness. In this study, based on the physiological regulation mechanism of blood pressure and state-of-the-art neuromodulation technique, we worked along with the vagus nerve stimulation scheme, developed and explored if and how a real-time neural recording and stimulation system could provide an insight into self-adaptive modulation in the blood pressure, in the hope to crack a crevice in the closed-loop treatment for resistant hypertension. Unlike the traditional neuromodulation devices, additional signal recording and real-time wireless transmission functions are added to the same device to realize the features of a dynamic monitor and modulator. The system is tested both in vitro and in vivo, showing decent electrical performance of 8 kHz sampling rate and flexible stimulation outputs which sufficiently covers our needs in manipulating neural activities of interest. A relatively stable drop in the blood pressure resulting from stimulation was observed and specific patterns in the vagus nerve signals relating to blood pressure could also be primarily identified. This laid a solid foundation for further studies on the final realization of closed-loop automatic adjustment for resistive hypertension treatment.